SOME PROBLEMS OF THE FORMATION OF THE FOLK LITERARY LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The folklore of the Kyrgyz is a special stage in the formation of a comprehensive and multifaceted literary language. The formation of an oral literary language is a syncretic literary work that has developed in all genres of lyrical and epic poetry, from folk rituals, traditional and folk songs, to proverbs, sayings, rhetoric, eloquence. It is known that at the stage of his oral creativity, the literary language went through very long and complex processes, and this has an impact on written literature and creative communication. The article deals with similar issues.
Keywords: Native language, Umaya mother, national language, literary language, folklore, ethnicity, people, nation, epic, lyrics, poetry, literature, etc